The role of social support in overcoming leisure constraints in recreational sport participation - Apostolia Ntovoli; Apostolia Ntovoli; Georgina Stavropoulou; Thomas Karagiorgos; Yannis Lianopoulos; Garyfallos Anagnostou; Elena Papacosta; Kostas Alexandris (Frontiers in Sports and Active Living)
IntroductionFollowing the hierarchical model of leisure constraints and the negotiation proposition, this study aimed to investigate whether individuals with different levels of leisure constraints exhibit varying scores in their perceived social support. By testing the relationship between constraints and social support, the study contributes to the literature by adding one more factor that determines the successful negotiation of leisure constraints.MethodsThe data were collected by an online survey with a convenient sample of the adult Greek population. The leisure constraint and the social support questionnaires were used to collect the data.ResultsThe cluster analysis revealed three groups with different leisure constraint scores. The group with the lowest constraint scores had the highest social support scores, while the group with the highest interpersonal scores had the lowest social support scores.DiscussionThese results further extend the hierarchical model of leisure constraints, showing that social support is one of the factors that should be included within the negotiation proposition. They interact with leisure constraints and determine their successful negotiation.